A study on depression among adolescents with asthma in South Korea using the 15th Korea Youth Risk Behaviour Web-Based Survey - Jin H Park (Korean Academy of Child Health Nursing, 2021)
Purpose This study investigated the factors that influence depression in adolescents diagnosed with asthma in South Korea, providing basic data supporting efforts to improve adolescents' mental health. Methods Multiple regression analysis was conducted on 4,020 subjects who had been diagnosed with lifelong asthma among the 57,303 respondents to the 15th Korea Youth Risk Behaviour Web-Based Survey from 2019. Results The participants were more likely to have depression if they were female, in middle school, their academic achievement was poor, they were drinkers or smokers, if they felt a very high amount of stress, and if they experienced very inadequate recovery from fatigue. Adolescents with asthma were 9.00 times more likely to experience depression when they felt a very high amount of stress (95% confidence interval [CI]=5.51-14.69, p<.001) than when they felt no stress. Conclusion Given these factors, measures to improve the mental health of adolescents should be developed and expanded, especially to decrease their stress levels. A separate program that is different from the school's regular health curriculum should be developed to manage the stress levels of adolescents with asthma, such as an after-school program or a program conducted at a local community centre.